Features of the species composition of fungi on plant and animal substrates of the Progress station (East Antarctica) - Karmanova, Veronika V.; Shabashova, Tatyana G.; Giginyak, Yury G.; Sinyavskaya, Marina G. (Experimental Biology and Biotechnology, 2023)
Mycofloristic and molecular genetic methods were used to study the species diversity of micromycetes on plant and animal substrates at the Progress station (East Antarctica). In total, 20 species of micromycetes from 10 genera and 2 phylums have been identified (the number of species in a separate sample varied from 1 to 4). A taxonomic analysis was carried out, the dominant species and temperature-dependent features of the growth of micromycetes were determined. It was revealed that 13 out of 20 identified species are anamorphs of micromycetes of the phylum Ascomycota. Most of the isolated micromycetes are psychrotolerant organisms.